The relationship between self-oriented perfectionism and exercise participation: based on the dualistic model of passion - Zhang, Weipeng; Zhu, Yuanjiao; Jiang, Feng; Song, Huitao (Frontiers in Psychology, 2024)
Background During the critical formative years of college, active participation in sports not only helps to alleviate stress, but also promotes the development of healthy habits. Although the multifaceted benefits of exercise have been widely recognized, there is a relative dearth of research on the relationship between personality traits, particularly college students’ self-oriented perfectionism (SOP), and exercise participation. Methods A questionnaire survey of 374 college students was conducted using the snowball sampling method. SPSS 26.0 and Mplus 8.3 were employed in this study to analyze the correlations between the variables, and on this basis, the effect of SOP on exercise participation was examined. The study also used 5,000 bootstrap samples and a 95% bias-corrected confidence interval to test the significance of the mediating effects. Results Correlation analysis showed that SOP was positively correlated with exercise participation. Harmonious passion and obsessive passion were positively correlated with SOP, and exercise participation. Further, the results of structural equation analysis revealed that SOP increased exercise participation. Harmonious passion and obsessive passion positively mediated the effect between SOP and exercise participation, respectively. Conclusion This study provides new perspectives to better understand college students’ exercise participation, emphasizing the importance of SOP and its influence on exercise participation through harmonious and obsessive passions. These findings have important implications for the development of effective exercise promotion strategies.